The use of peer questioning in foreign language classes at university - Elena A. Kurchenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Students currently studying at universities are representatives of generation Z, who have been accustomed and adapted to communication online since childhood using instant messengers and smartphone applications. In the age of digital technology, one of the pressing tasks in educating the younger generation is teaching them personal communication. The aim of this research is theoretical substantiation of the importance, description of the practice of application and experimental test of the peer questioning technique in foreign language classes with information technology students. Peer questioning refers to techniques used as interactive methods of teaching a foreign language. Interactive learning is a mandatory requirement of the Federal State Educational Standard for higher professional education of the latest generation. The main results of this work were: the structure design, the preparation stages, methodology for conducting and evaluating the technique of peer questioning of lexical material as a form of teaching a foreign language to students the of Mathematics and Information Technologies Institute at the Federal State Autonomous Educational Institution of Higher Education «Volgograd State University». The paper describes the main features of conducting a peer questioning and its advantages in the development of professional foreign language competence of students. Methods such as review and theoretical analysis of scientific literature, generalization of scientific information, and experimental method were used as research tools. As a result of the study, the use of peer questioning technique was proposed as one of the forms of interactive teaching a foreign language, which contributes to more effective learning of scientific and technical terminology.